1999
DOI: 10.1006/jcta.1999.2970
|View full text |Cite
|
Sign up to set email alerts
|

Fissions of Classical Self-Dual Association Schemes

Abstract: We describe fission schemes of most known classical self-dual association schemes, such as the Hamming scheme H(n, q) when q is a prime power. These fission schemes are themselves self-dual, with the exception of certain quadratic forms schemes in even characteristic.1999 Academic Press 1. THE HAMMING SCHEME The Hamming scheme H(n, q) is defined on vertex set X n of words of length n from an alphabet X of size q. Two words are in relation R i if and only if they differ in precisely i positions (we also say the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…There is no amorphic association scheme on 36 vertices with valencies 5, 15, and 15. This follows from the result by Bussemaker, Haemers and Spence [10] that there is no strongly regular (36,20,10,12) graph with a spread (a partition of the vertices into 6-cliques). The existence of one of the remaining association schemes on 36 vertices would imply an orthogonal array OA(6, m) with m 4.…”
Section: Classification Of Small Amorphic Association Schemessupporting
confidence: 63%
See 1 more Smart Citation
“…There is no amorphic association scheme on 36 vertices with valencies 5, 15, and 15. This follows from the result by Bussemaker, Haemers and Spence [10] that there is no strongly regular (36,20,10,12) graph with a spread (a partition of the vertices into 6-cliques). The existence of one of the remaining association schemes on 36 vertices would imply an orthogonal array OA(6, m) with m 4.…”
Section: Classification Of Small Amorphic Association Schemessupporting
confidence: 63%
“…An interesting example which was already observed in [12] is a partition of PG(2, 4) into two hyperovals ((0, 2)-sets of size 6) and a unital ((1, 3)-set of size 9). This gives a 3-class amorphic association scheme of negative Latin square type on 64 vertices with valencies 18, 18, and 27.…”
Section: Disjoint (M N)-sets In Projective Planesmentioning
confidence: 95%
“…This paper is a sequel to [4]. In that paper, it was observed that almost all known selfdual classical association schemes have natural fission schemes (fissioning the maximumdistance relation only); whereas in the non-self-dual case there seemed to be no analogous fission schemes.…”
Section: The Constructionmentioning
confidence: 93%
“…It We may conclude that disjoint (m, n)-sets of the form as described above give rise to amorphic association schemes. An interesting example which was already observed in [12] is a partition of PG(2, 4) into two hyperovals ((0, 2)-sets of size 6) and a unital ((1, 3)-set of size 9). This gives a 3-class amorphic association scheme of negative Latin square type on 64 vertices with valencies 18, 18, and 27.…”
Section: Disjoint (M N)-sets In Projective Planesmentioning
confidence: 99%
“…In any other example of a decomposition into four strongly regular graphs at least two of the graphs must be primitive. The following parameter sets seem feasible for such a decomposition: on v = 40 vertices: three graphs have parameters (40,12,2,4), the remaining graph is a disjoint union of 4-cliques; on v = 45 vertices: three graphs have parameters (45,12,3,3), the remaining graph is a disjoint union of 9-cliques; on v = 50 vertices: three graphs have parameters (50, 7, 0, 1), i.e. they are Hoffman-Singleton graphs, the remaining graph has parameters (50,28,15,16).…”
Section: Decompositions Into Four Strongly Regular Graphsmentioning
confidence: 99%